Hope in Janusz Korczak's Pedagogy of Realistic Idealism. Issue 3 (27th May 2017) - Silverman, Marc
Abstract: This article explores the approach of "Realistic Idealism" to moral education developed by the humanist-progressive moral educator Janusz Korczak, and the role hope plays in it. This pair of terms seems to be an oxymoron. However, their employment is intentional and the article will demonstrate their dialectical interdependence: "Idealism" encapsulates the educative drive to humanize the world and "Realistic" sets up empirically verifiable, ethical limits to idealistic strivings, and serves as an antidote to the dangerous pitfalls into which romantic and mystical forms of it fall.